Factors affecting financial well-being among Nigerian students in a public university in Malaysia - Chikezie, Obilaonu Columbus (2017)
Due to the high cost of living in Malaysia many students have become more concerned about their financial well-being and more careful with their spending in order to have a comfortable life or live comfortably in the future. There is need for everyone to have proper understanding of issues related to financial management and well-being because financial challenges do not only affect university/college students but also workers and other individual that low, middle and high income earners. The purpose of this study is to examine the factors that determine the financial well-being of Nigerian students studying in Malaysia. The sample of the study was 420 Nigerian postgraduate and undergraduate students in Universiti Putra Malaysia. Through the use of stratified sampling technique, the sample for this study was selected. Data were collected using structured questionnaire which were directly administered to the respondents by the researchers. The collected data were analyzed using descriptive and inferential statistics which include Pearson’s correlation test, independent sample t-test, Analysis of Variance (ANOVA) and multiple regression on Statistical Package for Social Science (SPSS). The relationship between financial literacy, money attitude, financial socialization, financial behaviour and financial well-being, was determined using Pearson correlation analysis, while ANOVA and one sample t-test was conducted to determine the difference in financial well-being based on demographic characteristics of the respondents. In identifying the determinants of financial well-being among the respondents of this study, multiple regression analysis was used. Results of this study showed that there was a significant relationship between financial well-being and financial socialization, financial behaviour and money attitude except for financial literacy which was not statistically significant. Multiple regression showed that six variables contributed significantly to the variance of financial well-being and they are financial behaviour, financial socialization, money attitude (effort), money attitude (obsession), money attitude (retention). In Conclusion, based on the findings of the study it can be said that only few Nigerian students in UPM had high level of financial well-being while the rest had moderate and low level. This means that there is still need for the money attitude, financial socialization and financial behaviour to be strengthened since they are part of the predicting variables of financial well-being among the respondents.